MOLECULAR DIVERSITY OF COMMON WHEAT INTROGRESSION LINES (T. AESTIVUM / T. TIMOPHEEVII) - I. N. Leonova; O. A. Orlovskaya; M. S. Röder; M. A. Nesterov; E. B. Budashkina (Вавиловский журнал генетики и селекции, 2015)
Genetic diversity of T. aestivum/T. timopheevii introgression lines was studied with regard to microsatellite loci and resistance to fungal diseases. Genotyping of hybrid lines and parental common wheat cultivars for 143 SSR markers revealed 521 and 440 alleles, respectively, or 3,24/2,73 alleles per microsatellite locus on the average. Comparison of genetic diversity indices of individual chromosomes revealed the lowest diversity for SSR loci on chromosomes 4D and 5D and the highest (0,62–0,67), on 5B and 6A. Evaluation of SSR polymorphisms and indices H in the three genomes of introgression lines indicated that the chromosomes of genome B had higher rates than A or D (B > A > D) which was probably a result of alien introgression into these chromosomes. Comparison of the results of molecular and phytopathological tests allows us to conclude that despite the severe selection for resistance to leaf rust in early generations and a large number of generations of selfing, the genetic diversity of introgression lines on microsatellite loci is preserved, which is indicative of the stability of alien genetic material in the common wheat genome.